2019
DOI: 10.1590/1678-4324-2019180579
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Thermal, Structural and Pasting Properties of Unconventional Starches from Ginger (Zingiber officinale) and White Yam (Dioscorea sp.)

Abstract: HIGHLIGHTS  Unconventional starches from ginger (Zingiber officinale) and yam (Dioscorea sp.) were investigated.  Lower thermal stability was found for unconventional starches when compared to maize starch.  Greater relative crystallinity and enthalpy of gelatinisation was recorded for ginger starch.  Yam starch had the highest peak viscosity, and corn starch had the highest breakdown. Oliveira, C.S.; et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
2
1
Order By: Relevance
“…Tus, ginger requires more cooking energy than onion, and it can be used in processing of food products under high temperature and acidic condition that requires high viscosity. A similar study on ginger starch reported a fnal viscosity of 2066.5 cps and pasting temperature of 89.42 °C [47], which is higher than the current study; this may be due to the use of pure starch from ginger rather than the whole ginger powder.…”
Section: Flowabilitycontrasting
confidence: 86%
“…Tus, ginger requires more cooking energy than onion, and it can be used in processing of food products under high temperature and acidic condition that requires high viscosity. A similar study on ginger starch reported a fnal viscosity of 2066.5 cps and pasting temperature of 89.42 °C [47], which is higher than the current study; this may be due to the use of pure starch from ginger rather than the whole ginger powder.…”
Section: Flowabilitycontrasting
confidence: 86%
“…It is utilized by petrochemical, pharmaceutic, construction, plastics, paint, and coating industries. Sodium oxide can be used in the production of alkali-activated materials [23] [24] [25]. Such applications' include alkali-activated slag (AAS) concrete, which is produced by using an alkali activator on ground granulated blast furnace slag, thereby reducing the effect of CO 2 emission by convectional cement industries.…”
Section: Components Of Sclerotium Of Pleurotus Tuber-regiummentioning
confidence: 99%
“…Zingiber officinale (ginger) is a rhizome that has been used in traditional medicine to treat different diseases like colds, bronchitis, cough, vomiting, and nausea [8][9][10]. Its composition includes components of phenolic (6-gingerol and its related compounds like shogaol) and terpene types (α-zingiberene, β-bisabolene), which have antioxidant properties [11][12][13]. Such properties are of interest from a technological and nutritional point of view.…”
Section: Introductionmentioning
confidence: 99%